PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY DISERTAI PICTORIAL RIDDLE TERHADAP KEMAMPUAN REPRESENTASI VERBAL MATERI GERAK LURUS SISWA DI SMA - Ratna Tri Mindi Sari; I Ketut Mahardika; Indrawati Indrawati (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstact: The research aimed to study the influence of guided inquiry learning with pictorial riddle for ability of verbal representation straigt motion matter for student in senior high school (SMA). The populated of this research was all student of class X in one of private senior high school in Pakusari. The eksperimental class taught using guided inquiry learning while the control class is taught employing a conventional learming model. Sampling is conducted adopting a cluster random sampling. The student pre-test and post-post test data ability of verbal representation was analyzed by independent sample t test on SPSS 23. The results of this research showed that guided inquiry learning with pictorial riddle for ability of verbal straigt motion matter for student in senior high school (SMA) is better than those learning with a conventional learning model.Keywords: guided inquiry, pictorial riddle, verbal representation